Components of Communication and Effective Service Delivery in Open Distance Learning Programmes in Southwest, Nigeria - ADEOLA FUNMILOLA AFONJA (Jurnal Pendidikan Nonformal, 2022)
Communication is germane to the management and success of every programme. Open and Distance learning institutions’ effort to positively reach out and go beyond imparting knowledge to their learners may never be realized without effective communication. Thus, the effective utilization of components of communication is important in the learning process. This study examined the relationship between the communication components in Open Distance Learning (ODL) institutions and effective service delivery of ODL programmes. Five objectives were developed to guide the study. The study adopted a mixed research design involving both qualitative and quantitative data collection techniques. 420 participants selected using a multi-stage sampling procedure involving both stratified random sampling and simple random sampling techniques. Both descriptive statistics and inferential statistics were used for data analysis.  The study, among other things, found a significant relationship between the communication components and the efficacy of the service delivery. Based on the findings, it was recommended that for service delivery to be effective, feedback mechanism must be varied, adequate and effective so that learners can use the one that best suit them; facilitators must be continuously trained on the use of different channels of communication to be able to produce and deliver quality content.